Kas yra prokalbė? (baltogermaniškoji problema) - Palmaitis, Letas (Baltistica, 1995)
PARENT LANGUAGE – WHAT DOES IT MEAN? Parent language is treated as a real dialectal zone of minimal innovations which migrates in time and space after sequential differentiation of dialects introducing more of innovations. Three last manifestations of the IE parent language have been Baltic, Balto-Slavic and Balto-Germanic.